Hubungan Antara Kecerdasan Emosi Dengan Self Control Siswa SMP X Kelas IX di Jakarta - Kodariyah (PIJAR: Jurnal Pendidikan dan Pengajaran, 2022)
The aim of this research is to determine the relationship between Emotional Intelligence and Self Control in Class IX Middle School Students in Jakarta. This research applies a quantitative approach with a correlational type of research. This correlational method aims to study the relationship between two or more variables, namely the extent to which changes in one variable are related to changes in other variables. Data collection was carried out through questionnaires. The data obtained was then analyzed using the Product Moment correlation approach, because both variables have a normal distribution. The questionnaire was distributed to 77 class IX respondents at SMP X in Jakarta. Based on the results of the data processing carried out, variable Meanwhile, for variable Y, namely Student Self Control, the highest number is in the high category at 64.9%, followed by the medium category level, and followed by the low category level. The correlation obtained between variables X and Y is 0.745 with a significance value of 0.000, which means the two variables have a positive relationship. The level of relationship is in the strong category because it is in the interval 0.60 – 0.799. Based on this explanation, the researcher concluded that there is a positive and significant relationship or correlation between Emotional Intelligence and Self Control in Students.